Gene expression profiling, prognosis, and immune microenvironment of KLF4 in malignancies - Shoukai Yu; Lingmei Qian; Tianlang Tong; Xujun Ma (PLoS ONE, 2025)
Gene expression profiling plays a crucial role in understanding the role of Krüppel-like factor 4 (KLF4) in the prognosis and tumor immune microenvironment of various malignancies. The transcription factor KLF4 plays a crucial role in various cellular processes, including cell differentiation, proliferation, and apoptosis. Genetic alterations and aberrant KLF4 expression have been observed in many malignancies, thus suggesting a potential role as a prognostic marker and therapeutic target. Herein, a systematic analysis of KLF4 genetic alterations revealed the mutation, amplification, and deletion frequencies across different cancer types. The genetic alteration patterns varied across malignancies, thus highlighting the diverse roles of KLF4 in different tumor contexts. Secondly, the prognostic significance of KLF4 expression was assessed in multiple cancers. High expression levels of KLF4 were associated with better clinical outcomes in kidney renal clear cell carcinoma, while low KLF4 expression correlated with a favorable prognosis in certain malignancies. In conclusion, the genetic alterations, dysregulated RNA expression, and prognostic implications of KLF4 in malignancies underscore its significance in cancer biology. The present findings will aid in understanding the role of KLF4 in tumor biology and its association with immune responses. Future investigations should focus on elucidating the functional roles and regulatory mechanisms of KLF4 to further assess its potential as a therapeutic target and predictive biomarker in cancer management.